Ethyl acetate fraction from Hibiscus sabdariffa L. attenuates diabetes-associated cognitive impairment in mice. (March 2018) - Seung, Tae Wan; Park, Seon Kyeong; Kang, Jin Yong; Kim, Jong Min; Park, Sang Hyun; Kwon, Bong Seok; Lee, Chang Jun; Kang, Jeong Eun; Kim, Dae Ok; Lee, Uk; Heo, Ho Jin
Abstract: The ameliorating effects of the ethyl acetate fraction from Hibiscus sabdariffa L. (EFHS) 2 against diabetes mellitus (DM) 3 and DM-induced cognitive impairment were investigated on streptozotocin (STZ) 4 -induced DM mice. The EFHS groups showed improved hyperglycemia and glucose tolerance compared to the STZ group. Furthermore, their liver and kidney function and lipid metabolic imbalance in the blood serum were effectively recovered. The EFHS groups significantly ameliorated STZ-induced cognitive impairment in Y-maze, passive avoidance, and Morris water maze (MWM) 5 tests. The EFHS groups showed significant improvement in the antioxidant and cholinergic systems of the brain tissue. In addition, EFHS had an excellent ameliorating effect on protein expression levels from the tau hyperphosphorylation pathways, such as phospho-c-Jun N-terminal kinases ( p -JNK), 6 phospho-tau ( p -tau), 7 and cleaved poly (ADP-ribose) polymerase (c-PARP). 8 The main compounds of EFHS were identified as various phenolic compounds, including hibiscus acid, caffeoylquinic acid (CQA) 9 isomers, and quercetin derivates. Therefore, EFHS containing various physiologically active materials can potentially be used for improving DM-induced cognitive impairment via its antioxidant activity, improvement of the cholinergic system, and hyperphosphorylation tau signaling. Graphical abstract: Highlights: The EFHS showed anti-hyperglycemic and anti-amnesic effects in STZ-induced mice. The EFHS efficiently improved anti-oxidant and cholinergic system. The EFHS showed inhibition of tau hyperphosphorylation pathway. Hibiscus acid, caffeoylquinic acid isomers, and quercetin derivates were identified.